Educação especial no município de Vitória/ES de 1989 a 2014 : políticas e direito à educação - Gobete, Girlene (2014)
This study aims at analyzing the special education policy in the City of Vitória, ES, Brazil between 1989 and 2012, considering the movement of legal and political changes at local and national level and the State's constitutional responsibility (in this case, the municipality as a federation member) for granting right to education of the group of students with disabilities, pervasive developmental disorders and high-potential or gifted. Based on these goals and taking into account the political and institutional organization of education in this municipality, the study focuses more specifically on 1 – Reassemble the conceptual and historical picture that based the special education policy between 2005 and 2012; 2 - analyze how the modality special education has been configured in the educational politics in the City of Vitória; 3 – discuss the devices created to ensure the right to education for the target group of students of special education; 4 - analyze the partnerships made between SEME and APAE/Vitoria in order to offer specialized service for the target group of students of special education enrolled in the public municipal school network. This study seeks to understand the execution of right to education based on the "logic" of interaction between the process of conquer and the prescription of citizenship rights (right), ensured/legitimated in the system of rules of a country (State) and granted by implementation of public policies. It relies on Norberto Bobbio‟s rights philosophy and contributions by national researchers and scholars who study the State responsibility for social rights and right to education, among them, José Silvério Baia Horta and Carlos Roberto Jamil Cury. In the field of special education, it discusses productions by researchers on special education policy, as well as legal texts that guide this modality and its movements for change, mainly after 2008, when Brazilian National Policy for Special Education was issued from the perspective of inclusive education, and its consequent decrees and resolutions. As theoretical-methodological basis, it adopted the Documental Analysis and Critical Discourse Analysis by Norman Fairclough. The study analyzes legal documents, official guidelines, statutes, and policies related to both public authority and the specialized institution. It shows the need of questioning the possibilities and challenges to consolidation of a new municipal public policy that meets the legal, administrative and pedagogical requirements in an inclusive education system that grants the right to education. Then, the “need” of partnership with the specialized institutions can be reconsidered. It highlights the policy potential to advance towards access, permanence and quality of education, as well as the challenges to be faced in order to achieve public education policies that meet the demands of the right to learn